Gender Differences in Academic Resilience and Well-Being among Senior High School Students in Ghana: A Cross-Sectional Analysis - Mustapha Amoadu; Edmond Kwesi Agormedah; Paul Obeng; Medina Srem-Sai; John Elvis Hagan; Thomas Schack (MDPI AG, 2024)
Senior high school (SHS) students are at risk of stress and other adverse exposures that may negatively affect their well-being and possibly cause attrition. The concepts of academic resilience and well-being share commonality as psychological attributes linked to positive functioning among students. Despite this connection, there seems to be limited research exploring these concepts across genders among SHS students in developing regions. This study examined the gender difference in academic resilience and well-being among SHS students in Ghana. Using a cross-sectional survey design, 190 SHS students in three schools from Kwahu North and South district (i.e., Afram Plains) of Ghana's Eastern Region completed the Academic Resilience Scale (ARS-30) and College Student Subjective Wellbeing Questionnaire (CSSWQ). The sample consists of 102 males and 88 females, with a mean age of 17.83 years. The data were analyzed using independent samples t-tests and hierarchical regression. The study established that students have a moderate level of academic resilience and a higher level of well-being, with no statistically significant variation in students' academic resilience (t = 0.718; p = 0.474) or well-being (t = −1.596; p = 0.112) across gender. Further, the study discovered that resilience significantly predicted academic well-being (B = 0.425; SE = 0.050; t = 8.50; p < 0.001). This study highlights the importance of promoting gender-sensitive intervention strategies that enhance the academic resilience and well-being of SHS students and help boost their educational attainment.